A clínica de família no Centro de Atenção Psicossocial III: psicose e configurações vinculares - Omena, Nara Amaral de (2014)
The objective of the present research was to analyze the links of families crossed by a psychotic crisis and the outcome of such crisis in the institutional care at CAPS (Centers of Psychosocial Attention), having the linkage clinic as focus. The framework proposed is the family clinic, apprehending the family as a founder of the subjectivity of the subject, a mediator between the subject and society, essential in the work with psychosis and consonant with the practices of care in the psychosocial attention in mental health. The methodology used was study of a clinical case based on the psychoanalytic method of investigation. From the analysis of the case presented, the family links and the family care were discussed. We have noticed that the group of family members was an important care asset for the family, from the listening of their suffering. Just as family therapy allows, in a unique way, the event and the intervention on the link configuration typical of the family, we believe that family therapy at CAPS, with the focus on link configurations, is essential to orient the practice of mental health care.